The great Arab conquests how the spread of Islam changed the world we live in - Kennedy, Hugh (Da Capo, 2007)
Examines the history of the great Islamic expansion,reveals how the Arab armies were able to overcome almost everything in their path, and brings to light the unique characteristics of Islamic settlement in new lands and the conversion to Islam of vast populations